CULTURE OF CONVERSATION AND SPEECH ACTIVITY - N. Mamasoliyeva (Bright Mind Publishing, 2025)
This article highlights the role and importance of communication culture as an important component of personal spirituality. Author etiquette, speech activity, speaking, listening and understanding processes human personality in formation instead analysis does. Oriental treatment culture, in particular Uzbek people for typical was speech manners and polite treatment to do importance is emphasized. In the text human speech, his/her spirituality and enlightenment determinant main criterion It is polite. to speak and from youth learnable upbringing product that is statement the language is treatment tool as place illuminated, our ancestor’s language and to the word respect with in a relationship to be about advice with is based on.
Keywords: Speech etiquette, oriental culture, oriental behavior, thinking, individual personality, literary language norms, etiquette, speech etiquette, language units, rules of behavior, customary rules , pronunciation culture of speech, lexical culture, clarity of speech, conciseness of speech, logic of speech, purity of speech, expressiveness of speech, attractiveness of speech, Speech culture, oratory, eloquence, expressiveness, rhetoric, ethics, psychology.